Structural Analysis of Bordetella Pertussis Biofilms by Confocal Laser Scanning Microscopy - Cattelan, Natalia (2018)
Biofilms are sessile communities of microbial cells embedded in a self-produced or host-derived exopolymeric matrix. Biofilms can both be beneficial or detrimental depending on the surface. Compared to their planktonic counterparts, biofilm cells display enhanced resistance to killing by environmental threats, chemicals, antimicrobials and host immune defenses. When in biofilms, the microbial cells interact with each other and with the surface to develop architecturally complex multidimensional structures. Numerous imaging techniques and tools are currently available for architectural analyses of biofilm communities. This allows examination of biofilm development through acquisition of three-dimensional images that can render structural features of the sessile community. A frequently utilized tool is Confocal Laser Scanning Microscopy. We present a detailed protocol to grow, observe and analyze biofilms of the respiratory human pathogen, Bordetella pertussis in space and time.